Starting travel health clinics in India: need, scope, structure and role of points of entry - Pasi, Achhelal Ramashankar (International Journal Of Community Medicine And Public Health, 2022)
Travel medicine is a new interdisciplinary field that has the ultimate goal to keep the travelers free from infectious diseases. Increase in international travel increases the risk of acquiring and transmitting travel-related illnesses and other health exposures. International travellers need to be adequately educated and advised by health care providers about potential health related risks. However, only a fraction of international travellers seeks pretravel health advice.Possible reason for not availing pretravel health services is non-availability of specifically trained health professionals to counsel patients on travel-related health risks. A pretravel individual health risk assessment, health checkups and counselling could be very beneficial to the traveler. In India, there are more than 40 points of entry (PoEs). These PoEs are evenly distributed across the country and have adequate infrastructure and trained manpower in accordance to the international health regulations (IHR)-2005. Resources (Infrastructure, trained manpower and experience of implementing international health) available at PoEs may be very well utilised to provide travel health services to international travellers.